Alternative feed raw materials modulate intestinal microbiota and its relationship with digestibility in Yellowtail Kingfish Seriola lalandi - CTM Dam; M Booth; I Pirozzi; Michael Salini; R Smullen; T Ventura; A Elizur (2020)
Gut microbiota plays a crucial role in nutrient digestibility and fish health. This study aimed to investigate the effects of alternative feed raw materials on the bacterial communities in the distal intestine and its relationship with nutrient digestibility in yellowtail kingfish (YTK), Seriola lalandi. Two 4-week digestibility trials were conducted to evaluate fish meal (FM), two sources of poultry by-product meal (PBM-1 & PBM-2), blood meal (BLM), faba bean meal (FBM), corn gluten meal (CGM), soy protein concentrate (SPC) and wheat flour (WH). The nutrient digestibility value was determined using the stripping fecal collection method. Bacterial communities were characterized by high-throughput sequencing based on V3-V4 region of the 16S rRNA gene. The most abundant phylum identified in the present study was Proteobacteria. A significant change in the distal intestine was observed in fish fed diets containing CGM and BLM, characterized by a reduction of species richness and diversity. Additionally, significant correlation between nutrient digestibility and intestinal microbiota was observed. Allivibrio, Vibrio, Curvibacter, Ruminococcaceae, and Clostridium were positively correlated, whereas Ralstonia genus was negatively correlated with nutrient digestibility. This study demonstrated that intestinal microbiota could be a useful tool for evaluating the digestibility of feed raw materials; however, further culture-based study is needed to confirm this observation.